Identifying measures for coverage of nutrition-sensitive social protection programs: Learnings from India - Nguyen, Phuong Hong; Avula, Rasmi; Neupane, Sumanta; Akseer, Nadia; Heidkamp, Rebecca (Wiley, 2024)
Optimal child growth requires a combination of nutrition-specific and sensitive interventions in the first 1,000 days. There is limited guidance on how to measure the population-level coverage of nutrition-sensitive social protection (NSSP), which is designed with explicit nutrition goals and often provides food or cash transfers and co-coverage with nutrition and health intervention. In this study in India, we designed a questionnaire that captures seven core NSSP program elements (transfer type, size, modality, population, timing, provider, conditionalities), then used cognitive testing to refine the questionnaire, and then implemented the questions as part of a telephone survey. Cognitive testing indicated variability in understanding the terms used to specify NSSP programs, including the need to use regional program names. Respondents also had difficulty recalling the timing of the benefit receipt. We included the refined NSSP coverage questions in a phone-based survey with 6,627 mothers with children <2 years across six states. Coverage of subsidized food was 73% across all households. Women were more likely to report receiving food than cash transfers during pregnancy (89% vs. 60%) and during lactation (75% vs. 13%). Co-coverage of NSSP with nutrition and health interventions during pregnancy (16%) and early childhood (3%) was low. It was feasible to measure coverage of NSSP investments in these populations; however, further research is needed to comprehensively assess all the dimensions of the NSSP benefits, including benefit adequacy and the validity of these questions when administered in person and by phone.